Reorganization of hydrogen bond network makes strong polyelectrolyte brushes pH-responsive - Wu, Bo (Sci Adv, 2016)
Weak polyelectrolytes have found extensive practical applications owing to their rich pH-responsive properties. In contrast, strong polyelectrolytes have long been regarded as pH-insensitive based on the well-established fact that the average degree of charging of strong polyelectrolyte chains is independent of pH. The possible applications of strong polyelectrolytes in smart materials have, thus, been severely limited. However, we demonstrate that almost all important properties of strong polyelectrolyte brushes (SPBs), such as chain conformation, hydration, stiffness, surface wettability, lubricity, adhesion, and protein adsorption are sensitive to pH. The pH response originates from the reorganization of the interchain hydrogen bond network between the grafted chains, triggered by the pH-mediated adsorption-desorption equilibrium of hydronium or hydroxide with the brushes. The reorganization process is firmly identified by advanced sum-frequency generation vibrational spectroscopy. Our findings not only provide a new understanding of the fundamental properties of SPBs but also uncover an extensive family of building blocks for constructing pH-responsive materials.